2020
DOI: 10.1002/mrd.23422
|View full text |Cite
|
Sign up to set email alerts
|

Toll‐like receptor 2 mediates the immune response of the bovine oviductal ampulla to sperm binding

Abstract: We previously reported that sperm binding to cultured bovine oviduct epithelial cells induces an anti-inflammatory immune response. Now we have developed a differentiated explant model to focus on the oviductal ampulla, where fertilization occurs, and to study the effect of sperm capacitation on the immune response. We used heparin to stimulate bovine sperm capacitation. Fluorescence imaging showed that 5,5ʹ,6,6ʹ-tetrachloro-1,1ʹ,3,3ʹ-tetraethylbenzimidazolyl-carbocyanine iodidelabeled sperm pretreated with (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…Increased expression level of TGFB1, as found in our pregnant group, is also present in bovine OECs cultured with embryos in vitro (81). However, it cannot be disregarded that the increase in TGFB1 levels is also related to sperm binding and induction of sperm-tolerance (80,82). Synergistically with TGFB1, the PTGES2, up-regulated in our pregnant group, participates in the eicosanoid metabolic process that will drive the production of PGE2 (83), promoting immune tolerance in the bovine oviduct (81,84).…”
Section: Discussionmentioning
confidence: 99%
“…Increased expression level of TGFB1, as found in our pregnant group, is also present in bovine OECs cultured with embryos in vitro (81). However, it cannot be disregarded that the increase in TGFB1 levels is also related to sperm binding and induction of sperm-tolerance (80,82). Synergistically with TGFB1, the PTGES2, up-regulated in our pregnant group, participates in the eicosanoid metabolic process that will drive the production of PGE2 (83), promoting immune tolerance in the bovine oviduct (81,84).…”
Section: Discussionmentioning
confidence: 99%
“…In line with their results, it can be indicated that a significantly high level of bFGF in EPC-CM activates the mRNA transcript levels of FGFR2/PTGS2 in cumulus cells and FGFR2/BMP15 in oocytes during IVM ( Figures 3, 6 and 7), which might modulate the cumulus expansion as well as high embryo developmental competence. IL-10 is an anti-inflammatory cytokine that plays an important role in regulating immune responses [67]. Bone marrow-derived macrophages co-cultured with EPC secreted a higher level of IL-10 than BMDM cultured alone in an in vitro system [68].…”
Section: Discussionmentioning
confidence: 99%
“…Initially, preliminary dose-dependent and time-dependent experiments were conducted to identify cytotoxic or detrimental effects of TLR2 antagonist and agonist on sperm motility and viability as analyzed by CASA and flow cytometry ( Supplementary Table S1 and Supplementary Figure S1 ). Next, based on our previous investigations ( Ezz et al, 2019 ; Akthar et al, 2019 ; Morillo, et al, 2020 ; Elesh et al, 2021 ) and our initial trials, the pre-treatment of sperm by TLR2 antagonist (100 µM) or agonist (100 ng ml −1 ) for 30 min was designated as an effective model to test our hypothesis without generating any cytotoxic or detrimental effects on sperm motility and viability.…”
Section: Methodsmentioning
confidence: 99%